Rome in the historical imagination of G. K. Chesterton’s Everlasting Man - Susan Hanssen (Church, Communication and Culture, 2020)
Roman civilization is at the heart of G.K. Chesterton’s historical imagination. Nowhere is this more evident than in his 1925 book The Everlasting Man, which challenged a materialist, evolutionary perspective on history and highlighted the distinctive place of the Christian Church in the development of civilization. By distinguishing between the ‘healthy heathenism’ of Rome and the ‘perverse paganism’ of Carthage, Chesterton shows how Rome became the setting for the Christmas story, which fulfills the natural religiosity of mankind and provides a center for the unified human story. Roman civilization as a chrysalis for Christianity is at the heart of Chesterton’s historical imagination.